Representation of Social Dynamics in the Travel Photography Works of Ranar Pradipto - Marcella Hana Tiara Putri; Supatmo Supatmo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
This study examines the digitalization motifs at the Tuha Indrapuri Mosque as a means of preserving traditional Acehnese visual arts. This mosque stands as a historical landmark that exemplifies the amalgamation of Hindu, Islamic, and local wisdom through its decorative motifs, which possess both aesthetic and religious significance. However, numerous of these motifs have suffered damage and are at risk of being lost due to a lack of comprehensive documentation. This study employed a descriptive qualitative methodology through literature review, observation, interviews, documentation, and visual digitization utilizing graphics software, resulting in two-dimensional and three-dimensional decorative motif designs. The research findings reveal that the decorative motifs at the Tuha Indrapuri Mosque comprise floral and geometric shapes that embody the aesthetic, symbolic, and spiritual values of the Acehnese people. Digitization serves as a strategic step to document and preserve traditional decorative motifs, ensuring their relevance in contemporary artistic developments. Practically, the outcomes of this digitization can be utilized as design assets for the creative industry, authentic references for future physical building restorations, and digital educational media that facilitate the younger generation’s access and learning about Acehnese cultural heritage visually.